Peran Kepolisian Terhadap Keadilan Restoratif Dalam Penganiayaan Menurut Peraturan Kepolisian Nomor 8 Tahun 2021 - Fathiyah Umaini; Rio Armanda Agustian; Toni (CV. Multi Kreasi Media, 2025)
Restorative justice in assault cases must consider the interests of the perpetrator, the victim, and the community as a whole. The role of the police can identify cases of assault that are suitable for the application of restorative justice. The purpose of this study is to determine and analyze the role of the police in the application of restorative justice in the resolution of assault crimes within the police force and to determine and analyze the factors that influence the role of the police in the application of restorative justice in the resolution of non-criminal assault within the police. The method used is empirical juridical. The results of this study show the role of the police as mediators or facilitators who encourage conversations between victims and perpetrators, conflict resolvers who focus on recovery-based solutions rather than punishments, justice guardians who support peaceful settlements, and prevent conflicts from developing further. The police must conduct an initial evaluation to determine the type of persecution that usually only applies to persecution that does not cause serious injury. Factors that affect the role of the police in the application of restorative justice in the crime of persecution are internal factors and external factors on the influence of the police in the application of restorative justice with cases of persecution.